Analysis of the UHRF1 expression in serum and tissue for gastric cancer detection. (May 2015) - Ge, Mengyuan; Gui, Zhen; Wang, Xiaoming; Yan, Feng
Abstract Objective: To analyze the Ubiquitin-like with PHD and ring finger domains (UHRF) 1 expression in gastric cancer (GC). Methods: The concentrations of UHRF1 DNA in serum were compared between 187 GC patients and 56 healthy controls using real-time PCR. Immunohistochemical analysis using tissue microarrays was performed. Results: UHRF1 DNA levels were significantly higher in GC patients compared to healthy controls (p < 0.001) and have associations with age and lymph node metastasis (LNM). The UHRF1 expression was significantly higher in tumor tissue than matched normal tissues (p < 0.001). Conclusions: The UHRF1 expression in serum and tissue may represent a novel biomarker for GC diagnosis and prognosis.